(Invited) Preparation of GaSb Surface for Low Interfacial Trap Density MOS Capacitors. (10th April 2015) - Chen, Chen-Yu; Hsueh, Wei-Jen; Chang, Chao-Min; Hsu, Hsien-Ming; Chyi, Jen-Inn
Abstract : The effects of i n-situ and ex-situ surface treatments on the electrical properties of GaSb metal-oxide-semiconductor capacitors (MOSCAPs) are compared and investigated. The in-situ approach can provide a native oxide-free GaSb surface subsequent high-κ dielectric deposition. HfO2 /Al2 O3 /p-GaSb MOSCAPs fabricated on an Sb-stabilized surface exhibit clear inversion at low frequency and good modulation of the Fermi level across the whole GaSb band gap. The interfacial trap density (Dit ) extracted by the conductance method is about 7.6×10 11 cm -2 eV -1 near the valence band. As to the ex-situ process, the air-exposed GaSb samples are treated by hydrogen plasma at room temperature prior to dielectric deposition. The capacitance-voltage (C-V) characteristics and gate leakage currents are comparable to those of the MOSCAPs prepared by in-situ method. Dit near the valence as low as 6.0×10 11 cm -2 eV -1 is obtained, indicating the feasibility of using GaSb p-channel MOSFETs for future complementary MOS integrated circuits.